Effects of Munc13-1 and Munc18-1 on dopamine secretion dysfunction in manganese-exposed SH-SY5Y cells - Changzhe LI; Chun YU; Hua ZHAO; Jun LI; Ting HU (环境与职业医学, 2023)
BackgroundNeurotransmitter secretion disorder induced by chronic manganese poisoning has always been one of the important causes of body injury, but the mechanism of neurotransmitter secretion disorder caused by manganese is not clear at present. ObjectiveTo investigate the effects of presynaptic membrane intracellular protein 13-1 (Munc13-1) and synapse fusion protein binding protein 18-1 (Munc18-1) on dopamine secretion dysfunction induced by manganese chloride (MnCl2) in human neuroblastoma (SH-SY5Y) cells. MethodsA SH-SY5Y cell model induced by MnCl2 was established. Cell viability was measured by MTT assay. Four experimental groups were set up: control group and low-, medium-, and high-dose manganese groups (0, 100, 200, and 400 μmol·L−1 MnCl2). They were treated with corresponding doses of MnCl2 for 24 h. The secretion of dopamine was measured by enzyme-linked immunosorbent assay. The mRNA expression of Syntaxin-1 was detected by real-time quantitaive PCR. Total cell proteins were extracted, and the protein expression levels of Munc13-1, Munc18-1, and Syntaxin-1 were detected by Western blotting. The correlations of MnCl2 exposure and dopamine secretion with the protein expressions of Munc13-1 and Munc18-1 were also analyzed by Pearson correlation. ResultsCompared with the control group, the cell viability rate decreased gradually with the increase of manganese exposure concentration, and the difference between the medium- and the high-dose manganese groups was statistically significant (P<0.05). The concentration of dopamine in cell culture medium of all manganese exposure groups decreased with the increase of manganese concentration, and compared with the control group and the low-dose manganese group, the medium- and the high-dose manganese groups were statistically significant (P<0.05). The expression of Syntaxin-1 at mRNA or protein level did not change significantly among groups (P>0.05). Compared with the control group, the protein expression of Munc13-1 decreased and that of Munc18-1 increased with the increase of manganese concentration (P<0.05). Compared with the low-dose manganese group, the changes of Munc13-1 protein in the high-dose manganese group and Munc18-1 protein in the medium- and high-dose manganese groups had statistical significance (P<0.05). Compared with the medium-dose manganese group, the protein changes of Munc18-1 in the high-dose manganese group were statistically significant (P<0.05). The correlation analysis showed that MnCl2 dose was negatively correlated with Munc13-1 protein expression (r=−0.898, P<0.05), and positively correlated with Munc18-1 protein expression (r=0.678, P<0.05). Dopamine secretion was positively correlated with Munc13-1 protein expression (r=0.932, P<0.05), and negatively correlated with Munc18-1 protein expression (r=−0.817, P<0.05). ConclusionThe inhibition of dopamine secretion in SH-SY5Y cells induced by manganese exposure is related to up-regulation of Munc18-1 and down-regulation of Munc13-1 expression levels, which may be one of the reasons for nerve injury caused by manganese.